2018
DOI: 10.1093/cercor/bhy097
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM Mutation Impairs Motor Cortex Network Dynamic and Voluntary Motor Functions

Abstract: While it is well known that netrin-1 and its receptors UNC5 and UNC40 family members are involved in the normal establishment of the motor cortex and its corticospinal tract, less is known about its other receptor Down syndrome cell adherence molecule (DSCAM). DSCAM is expressed in the developing motor cortex, regulates axonal outgrowth of cortical neurons, and its mutation impairs the dendritic arborization of cortical neurons, thus suggesting that it might be involved in the normal development and functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Furthermore, in many models of neurodevelopmental disorders, altered excitation and altered anatomical characteristics of cortical pyramidal neurons go hand-in-hand. For example, DSCAM model mice have impaired neocortical pyramidal dendritic arborization [ 49 ] as well as reduced neocortical excitability in vivo [ 36 ]. Thus, losing an important overall anatomical pattern among Itgb3 mutant neurons may also have concomitant physiological and behavioral aberrations, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in many models of neurodevelopmental disorders, altered excitation and altered anatomical characteristics of cortical pyramidal neurons go hand-in-hand. For example, DSCAM model mice have impaired neocortical pyramidal dendritic arborization [ 49 ] as well as reduced neocortical excitability in vivo [ 36 ]. Thus, losing an important overall anatomical pattern among Itgb3 mutant neurons may also have concomitant physiological and behavioral aberrations, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in vertebrates and invertebrates has revealed roles for DSCAMs in several neurodevelopmental processes, including synaptogenesis, neural proliferation, dendritic selfavoidance, cell sorting, and axon growth, guidance, and branching (Chen et al, 2006;Fuerst et al, 2008Fuerst et al, , 2009Liu et al, 2009;Maynard and Stein, 2012;He et al, 2014;Dascenco et al, 2015;Thiry et al, 2016;Laflamme et al, 2019;Sachse et al, 2019). In the mouse retina, loss of Dscam or Dscaml1 leads to excessive dendritic fasciculation and somatic clustering of the cell types that normally express these molecules, demonstrating a role in dendritic self-avoidance and tiling (Fuerst et al, 2008(Fuerst et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous Dscam null mutation occurring in mice (Dscam del17 ) leads to the early post-natal emergence of uncoordinated movements; as adults, these animals additionally display severe hydrocephalus, seizures, aberrant locomotion, and impaired motor learning (Fuerst et al, 2008;Xu et al, 2011). Similarly, mice carrying a different Dscam null mutant allele (Dscam 2J ) present dystonic hypertonia and deficits in locomotor coordination related to abnormalities in central sensorimotor circuitry (Fuerst et al, 2010;Lemieux et al, 2016;Thiry et al, 2016Thiry et al, , 2018Laflamme et al, 2019). Viability of Dscam null mutant mice is highly affected by their genetic background, leading to early post-natal lethality in a C57BL/6 background but survival to adulthood in an inbred C3H background, which suggests that modifier genes partly compensate for early developmental roles of DSCAM (Fuerst et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If cortical neurons project normally through the commissure upon Dscam knockdown, the density of axonal commissural branches is decreased in the cortical grey matter of the contralateral cortex [38]. Similarly, anterograde tracing studies have also shown that corticospinal tract axons of the motor cortex of Dscam 2J mutant mice decussate normally at the level of the medulla and project normally in the contralateral spinal white matter [51], but their axonal terminals exhibit an aberrant branching within the dorsal spinal grey matter. Taken together, these findings suggest that DSCAM contributes to axonal growth, fasciculation, and branching, but not guidance.…”
Section: Axonal Guidance Growth Fasciculation and Branchingmentioning
confidence: 99%
“…The Dscam 2J mutant spinal cord exhibits a decrease in the density of glutamatergic pre-synaptic boutons of peripheral sensory afferents onto motoneurons, and a reduced monosynaptic sensorimotor reflex during development and through adulthood [30]. Furthermore, Dscam 2J mutation also alters the intracortical circuitry of the motor cortex by decreasing the density of intracortical and thalamocortical inputs onto cortical and corticospinal neurons, and by impairing intracortical processing in response to low-and high-frequency stimulation [51], thus preventing short-term plasticity and synaptic integration at the cortical level.…”
Section: Establishment and Maintenance Of Synaptic Functionsmentioning
confidence: 99%